A membrane filtration method for the enumeration of Escherichia coli in bathing water and other waters with high levels of background bacteria - Merel A. Kemper; Christiaan Veenman; Hetty Blaak; Franciska M. Schets (IWA Publishing, 2023)
The presence and level of faecal indicator bacteria are important factors in estimating the microbiological quality of surface water and the risk of human infection upon exposure to this water. Until 2014, ISO 9308-1:2000 was available and used to enumerate faecal indicator Escherichia coli in bathing water. In 2014, this ISO was technically revised and replaced by ISO 9308-1:2014. This ISO introduced a less selective method for enumeration of E. coli that allows non-specific growth from waters containing high levels of bacteria, such as surface waters. This implies that currently there is no suitable reference membrane filtration method for the compliance monitoring of official bathing sites for E. coli according to the European Bathing Water Directive. Here, the performance characteristics of three chromogenic culture media, namely Tryptone Bile X-glucuronide (TBX) agar, Chromogenic Coliform Agar (CCA), and CHROMagar E. coli/Coliform (ECC) were investigated at 44 °C for water with varying levels of bacteria according to ISO 13843:2017. Based on performance characteristics, colony counts, and practical usage, TBX appeared the most suitable culture medium for the enumeration of E. coli in bathing water and other waters with high levels of background bacteria, such as surface water in agricultural areas and wastewater discharge points. HIGHLIGHTS Performance characteristics at 44 °C, after resuscitation at 36 °C, were comparable for the tested chromogenic culture media TBX, CCA, and ECC.; Based on performance characteristics, colony counts, and practical usage, TBX was selected as the preferential culture medium.;